MiR-100 Suppresses the Proliferation, Invasion, and Migration of Hepatocellular Carcinoma Cells via Targeting CXCR7. (19th July 2021) - Ge, Yiman; Shu, Jia; Shi, Gang; Yan, Fuguo; Li, Yejing; Ding, Hangliang
Abstract : This study is to elucidate the functions of miR-100 in hepatocellular carcinoma progression and to explore the underlying mechanisms. Expression levels of miR-100 in normal-cancer hepatocellular carcinoma tissues were measured using quantitative real-time PCR (qRT-PCR). The invasive and proliferative abilities of hepatocellular carcinoma cell lines transfected with mimic-NC or mimic-miR-100 were measured using transwell, CCK-8, and colony formation assays. The binding sites between CXCR7 and miR-100 were determined using luciferase reporter assays. The correlation of CXCR7 and miR-100 in hepatocellular carcinoma progression was further confirmed by cotransfection assays. Our results showed that miR-100 was significantly lower expressed in hepatocellular carcinoma tissues and negatively associated with CXCR7 expression. Cell functional assays' results found that upregulation of miR-100 inhibited the proliferative, invasive, and migrative abilities in hepatocellular carcinoma cells. Luciferase reporter assay suggested that CXCR7 mRNA and miR-100 bound one another. Increasing CXCR7 expression reversed the inhibitive effects of upregulated miR-100 in hepatocellular carcinoma cells. Further study showed that miR-100/CXCR7 played a role in hepatocellular carcinoma progression by regulating metalloproteinase-2 (MMP2) and vascular endothelial growth factor (VEGF). Conclusively, miR-100 exerts antitumor effects on hepatocellular carcinoma. Overexpression of miR-100 attenuates the invasive and proliferative abilities of hepatocellular carcinoma cells by targeting CXCR7.